Designing and Prototyping Interfaces with Figma : learn essential ux/ui design principles by creating interactive prototypes for mobile, tablet, and desktop - Staiano, Fabio, ....- (Birmingham : Packt Publishing Ltd., 2022)
Figma is a great design tool for anyone looking to create a user interface using innovative features and real-time collaboration. This book covers the basics of UX research in FigJam and the process of creating a complete design using Figma tools and features. You'll be able to create your own interactive user interface in Figma from the ground up.
Keywords: Informatica; Programmeren; Webdesign